Talking new politics (New Dehli, 2005)
The essays in this book are an outcome of discussions that took place in the fourth World Social Forum, held in Mumbai in January 2004. They offer the reader different and complex ways of understandings the processes that have helped to shape the World Social Forumand the new politics that seems to be emerging and what all this represents, forlife, society, and politics more generally.
Keywords: "Social change, Social prediction"